Analisis Kepuasan Pemustaka Terhadap Kinerja Pengelola Perpustakaan Fakultas Adab Dan Humaniora UIN Raden Fatah Palembang Melalui Teori The Big Five Personality - Solehati, Indah; Rusmiatiningsih, Rusmiatiningsih (Nusantara Journal of Information and Library Studies (N-JILS), 2024)
The efficiency of the library's current operations is significantly impacted by the performance of its managers. In an attempt to raise the caliber of librarian performance, this study examines the analysis of librarian satisfaction with the work of library managers at the Faculty of Ethics and Humanities, UIN Raden Fatah Palembang. The purpose of this study is to determine the degree of user satisfaction and assess how well librarians and other library managers have performed in meeting users' expectations by analyzing library managers' personalities through librarians' performances and applying The Big Five personality theory. A quantitative technique is employed in the research, and questionnaire surveys are performed to obtain research data. The questionnaire consists of 5 main indicators using The Big Five Personality Theory and each main indicator consists of 4 questions. The sample used in this research was 34 respondents who were students of the Faculty of Adab and Humanities who were registered as users at the Faculty of Adab and Humanities Library. Keywords: User’s Satisfaction, Librarian Performance, Personality, The Big Five Personality ABSTRAK   Kinerja pengelola perpustakaan sangat berpengaruh keoptimalan kegiatan yang ada di perpustakaan. Penelitian ini mengkaji Kepuasan Pemustaka Terhadap Kinerja Pengelola Perpustakaan Fakultas Adab Dan Humaniora UIN Raden Fatah Palembang sebagai upaya meningkatkan kualitas kinerja pustakawan. Tujuan penelitian ini ialah mengidentifikasi tingkat kepuasan pemustaka serta mengevaluasi sejauh mana pustakawan dan pengelola perpustakaan lainnya telah memenuhi ekspektasi pemustaka dengan mengkaji kepribadian pengelola perpustakaan melalui kinerja pustakawan dengan mengimplementasikan teori kepribadian The Big Five. Pada penelitian pendekatan yang digunakan adalah metode pendekatan Kuantitatif dengan metode pengumpulan data penelitian menggunakan Survey Kuesioner. Kuesioner terdiri dari 5 indikator utama dengan menggunakan Teori The Big Five Personality dan masing-masing indikator utama terdiri dari 4 pertanyaan. Sampel yang digunakan dalam penelitian ini sebanyak 34 Responden yang merupakan Mahasiswa Fakultas Adab Dan Humaniora yang terdaftar sebagai pemustaka di Perpustakaan Fakultas Adab Dan Humaniora.